HINDU NATIONALISM, MODI FACTOR AND THE IDEOLOGY MATRIX IN CONTEMPORARY INDIA - Raja Qaiser Ahmed (Margalla Papers, 2020)
Hindutva has become a social reality with its overarching imprints on Indian polity and its subsequent reflection on India’s political landscape. The revocation of Article 370 and the amendment in the Citizenship Amendment Bill are symptomatic of these undercurrents. The domestic underpinnings under Modi had been primarily guided by the Hindu nationalistic narrative. The non-acceptance and non-accommodative overtures in the guise of majoritarian values spearheaded India’s transition into a narrow and parochial polity. The Modi phenomenon dwindled the construction of Nehruvian state based on mutual coexistence and composite culture. This paper attempts to dissect BJP’s ideology matrix and its historical evolution. It explicates the manifestation of Hinduness in the tenure of Modi government from 2014 onwards. It further delineates the emerging contours of state and society in India and analyzes the contemporary ideological undercurrents within India.